2010
DOI: 10.1021/es903240g
|View full text |Cite
|
Sign up to set email alerts
|

PBDEs in 2−5 Year-Old Children from California and Associations with Diet and Indoor Environment

Abstract: This study determined the body burden of PBDEs in 100 California children, and evaluated associations with sociodemographic, household, and dietary factors. In national and international comparisons, California dust, breast milk, and human serum samples contain higher concentrations of PBDEs. Higher levels in children suggest exposure pathways depend upon age. Plasma samples were analyzed for PBDEs using GC/MS. Circulating levels of PBDEs were ten-to 1000-fold higher than similar aged populations in Mexico and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
94
6
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 46 publications
13
94
6
1
Order By: Relevance
“…We also did not measure some higher-brominated compounds (e.g., , which are present in decaBDE. Another study, however, indicates that BDE-209 represents a very small fraction of total serum PBDE concentrations in a different population of California children (Rose et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…We also did not measure some higher-brominated compounds (e.g., , which are present in decaBDE. Another study, however, indicates that BDE-209 represents a very small fraction of total serum PBDE concentrations in a different population of California children (Rose et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to other persistent organic pollutants, the highest body burdens of PBDEs are found in infants and toddlers, due primarily to exposure to maternal milk and house dust containing PBDEs (Costa et al 2008;Fischer et al 2006;Rose et al 2010;Schecter et al 2004). These findings are of concern since a study of New York City children ≤ 72 months of age found that lower scores on tests of cognitive, behavioral, and physical development were associated with higher levels of PBDEs in cord blood, which was used as a measure of peri natal exposure (Herbstman et al 2010).…”
mentioning
confidence: 99%
“…Differences in chemical body burdens are correlated with not only socio-economic status (Zota et al 2010a, MacKendrick 2014 but also race/ethnicity and geographic location. People with lower income levels had higher levels of BFR exposure (Zota et al 2010b); children with mothers and caregivers who have lower education levels had higher body burdens (Rose et al 2010); and in California, Black and Hispanic children had higher body burdens than White and Asian children (Windham et al 2010). Exposures to phthalates are also correlated with race/ethnicity (Trasande et al 2013).…”
Section: The Rise Of Precautionary Consumptionmentioning
confidence: 99%